Pneuma and realized eschatology in the book of wisdom - Edwards, Matthew (Forschungen zur Religion und Literatur des Alten und Neuen Testaments, 2012)
Cosmic wisdom Understanding an ancient Jewish stoic concept.The Book of Wisdom s understanding of Israel s history, of contemporary politics and of the immortal fate of the persecuted sage can be understood to be part of one theological system. This system integrates texts and concepts from Jewish Wisdom, the biblical narratives of the patriarchs from Adam to Moses, eschatological hope and apocalyptic language, an understanding of the spirit of God in the enabling of prophets and leaders and, most distinctively, the Stoic concept of pneuma. This last concept unites the biblical resources and allows Wisdom, using eschatological language, to speak of the ordering of the cosmos for the judgement for the wicked and the exaltation of God s people in the present age Matthew Edwards addresses first the question of the literary unity of Wisdom. This is followed by an examination of the differing uses of the term pneuma within Wisdom, that is as divine agent of salvation, the means of the ordering the cosmos and the substance from which souls are composed. The nature of personal salvation within Wisdom is also considered and shown to be an integral part of the understanding of the cosmos, ordered for judgement and exaltation. Finally, this notion of the ordering of the comos and history for God s people is discussed with its consequences for Jewish life under contemporary Hellenistic and Roman rule.